Computational studies of folding and binding of polypeptides - Turpin, Eleanor R. (2013)
In this thesis molecular dynamics simulations, in conjunction with the complementary methods of docking and QM-MM, are used, and further developed, to study two unusual polypeptide systems: the conformational preferences of isomers of an antibiotic peptide and the binding behaviour of a human transporter protein. The antibiotic peptides are analogues of a naturally occurring antibacterial called nisin which has a biological function dependent on the formation of five macrocyclic rings closed by a thioether bond between modified L-amino and D-amino residues. We propose analogues where the thioether bond is replaced by a disulfide bond between cysteine residues and the chirality of the cysteines is altered. The conformational preferences of the nisin analogues, and the dependence of ring formation on cysteine chirality, are characterised using molecular dynamics. An analogue (D-Cys3-D-Cys7-L-Cys8-L-Cys11) is identified that favours the simultaneous formation of the S3-S7 and S8-S11 disulfide bonds and has an RMSD of 0.6 Å to 1.7 Å between the centroids from clustering the MD trajectories and an NMR structure of wt-nisin. The nisin analogues contain unusual D-amino residues and using explicit solvent MD simulations of four polypeptides, it is shown that the (φ, ψ) → (-φ, -ψ) transformation of the CMAP term in the CHARMM potential energy function leads to sampling of conformations which are closest to X-ray crystallographic structures for D-amino residues and that the standard CMAP correction destabilises D-amino β-sheets and β-turns.